INTERNALIZATION OF MULTICULTURAL VALUES IN THE LEARNING PROCESS OF ISLAMIC RELIGIOUS EDUCATION - Dhikrul Hakim (Journal Education Multicultural of Islamic Society, 2022)
Abstract This research aims to describe, analyze and interpret the multicultural values contained in the learning process of Islamic Religious Education. The internalization process of multicultural values in the learning process of Islamic Religious Education. The internalization model of multicultural values in the learning process of Islamic Religious Education at Muhammadiyah Vocational High School 1 Ngoro. This research used a qualitative type with Crasswell's realist ethnographic approach. Data collection techniques used participant observation techniques, in-depth interviews, and documentation. Informant determination technique used purposive sampling and snowball sampling techniques. Data analysis techniques used J.Spreadly analysis techniques, which perform four-step analysis: domain analysis, taxonomic analysis, component analysis, and cultural theme analysis. While the technique tests the validity of data using methods of triangulation of sources, methods, and theories. The results of this research are the first, multicultural values contained in the learning process of Islamic Religious Education at SMK Muhammadiyah 1 Ngoro are honest, disciplined, responsible, caring, polite, environmentally friendly, mutual cooperation, collaboration, peace-loving, responsive and pro-active. The second, The internalization process of multicultural values in the learning process of Islamic Religious Education at SMK Muhammadiyah 1 Ngoro Jombang through three different processes in the internalization of these values are processes through transparency; the teachers become models or examples for students. Through habituation, prayer at the beginning of lessons, habituation of congregational dhuha prayer, congregational dhuhur prayer, and congregational Friday prayers, clean and healthy living culture, 3S culture (Smile, Greetings, Salim). Cultivate a skilled and independent attitude through equality in association with democratic attitudes, attitudes of togetherness, attitudes of respect for differences and diversity in association. The third, the internalization model of multicultural values in the learning process of Islamic Religious Education in SMK Muhamadiyah 1 Ngoro Jombang based on data and analysis of researchers. The theoretical findings of this study are that Researchers named the Cross Culture and Religion Model. There are three forms, namely with the Islamic Religious Education Learning Process by including the K13 curriculum in subjects with multicultural values as in core competence and basic competence. With habit forming, consistent and programmatic learning: Consistent in moral development, language skills and worship. Programmatically carry out coaching activities regularly and periodically. By the examples, the teacher's example in morals, manners, and good habits that are taught and familiarized with the real examples practiced by students in school until returning home.Keywords:Ã‚Â  Internalization of Values, Multicultural Values, Learning Process of Islamic Religious Education.